2021
DOI: 10.28991/cej-2021-03091757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Animal Bone Ash on the Mechanical Properties of Asphalt Concrete

Abstract: For the sake of enhancing the mechanical properties and durability of asphalt concrete, many studies suggest adding different admixtures, such as waste materials in the form of filler. These admixtures have a significant influence on the performance of asphalt concrete by plying a roll in filling the voids between particles and sometimes as a cementitious material. This study aims to improve the strength of asphalt concrete by adding crushed animal bone to the mix after carbonization at a temperature of 800 Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The small differences in the values for consistency, setting times, density, water-absorption and compressive strength was accounted for due to the difference in fineness. PABA produced more fines than PAB because of the temperature the bones were subjected to during the ashing process [17].…”
Section: Discussionmentioning
confidence: 99%
“…The small differences in the values for consistency, setting times, density, water-absorption and compressive strength was accounted for due to the difference in fineness. PABA produced more fines than PAB because of the temperature the bones were subjected to during the ashing process [17].…”
Section: Discussionmentioning
confidence: 99%
“…Al-hasan et al [ 4 ] used recycled coarse aggregate and polymer to prepare environmentally friendly pavement, which effectively improved the durability of asphalt pavement. Kadhim et al [ 5 ] used animal ashes in different proportions to replace limestone to prepare asphalt mixture. It was found that when 20% animal ashes were used to replace limestone, the mechanical properties of the asphalt mixture were improved, so as to improve the durability.…”
Section: Introductionmentioning
confidence: 99%